Smart grid inspired future technologies : second EAI International Conference, SmartGIFT 2017, London, UK, March 27-28, 2017, Proceedings /: second EAI International Conference, SmartGIFT 2017, London, UK, March 27-28, 2017, Proceedings. (2017) - Unknown
No abstract available